Determination Of Prescription Dose Around The Target Using Tps 3d Ocentra 4.5.3 On Ca-Thyroid - Dezy Zahrotul Istiqomah Nurdin; Ayu Sita Dianti Agistya Putri; Haruming Sekar Siam Duta Purnama; Perwira Annissa Dyah Permatasari; Winarno Winarno; Bambang Haris Suharmono (Jurnal Biosains Pascasarjana, 2022)
Determination of the therapeutic dose (Prescription Dose) around the target using 3D TPS in the case of Ca-Thyroid is used to perform contouring in 3D form of a Ca-Thyroid target volume so that at the time of treatment the right dose can be obtained to kill the target. but also minimize the effects received by OAR. So it is necessary to know the stages in determining the therapeutic dose using TPS in 3D with the software used is Oncentra. This research was conducted using the observation method and the interview method with the field supervisor. From this research, it was found that TPS 3D CRT is a technique of CT planning so that the isodose curve can be formed according to the shape of the target volume. Determination of the therapeutic dose (prescription dose) can be carried out in four stages, namely the initial stage (opening the program), initial planning (contouring internally and externally), planning beam, and dose calculation. So that from the four stages, the dose per fraction of OAR is 2.01 Gy right eye, left eye 0.73 Gy, right eye lens 0.45 Gy, left eye lens 0.19 Gy, and spinal cord 1.8 Gy. . While the dose per fraction for the target volume is GTV 2.77 Gy, PTV 2.92 Gy, and CTV 2.83 Gy.